A case study of professional growth of Cross-Disciplinary Preschool Education Master students - Li, Fanfan; Boon, Ng Soo (Southeast Asia Early Childhood Journal, 2021)
China entered the baby boom era with the announcement of Second Child Policy in 2015, this has led to increase of child birth rate and subsequently a growing shortage of preschool teachers. To solve this issue, Chinese State Council drafted the policy proposal on training of cross-disciplinary talents in higher education allowing people with different bachelor degree to become preschool teachers. Cross-Disciplinary Preschool Education Master Degree (CDPEM) program offered in some universities is an outcome of this policy. The purpose of this study is to explore in depth professional growth experiences of these CDPEM students. Findings of the study can be input to decision of the continuity of this policy. The study was conducted using qualitative research method. In-depth interviews of three Chinese CDPEM participants were used to collect data. These three CDPEM participants respectively have Chinese Literature, English Education and Applied Chemistry background. Findings is discussed according to the characteristics of professional growth, personalities and experiences, and strategies to overcome problem faced during the Master course. The results of professional growth experiences are summarized into four themes: professional attitude and motivation, professional ability, professional knowledge and professional philosophy. Data analysis indicated that these three CDPEM students have strong desire of professional development, and consistently striving for professional identity, however they have low self-efficacy, perceived weak professional knowledge, perceived lack of professional ability and poor research ability. The background knowledge from Bachelor degree, real-life experience, inherent motivation and attitude towards learning influence their professional development in the course. These students develop their own authentic internal strategies towards ascertaining professional identity. The external strategies are cultivation of research ability and internship as well as participation in universities joint projects. The policy of CDPEM is feasible as a short-term measure to counter shortage of preschool teachers however the shortcomings need to be overcome to ensure quality of preschool teachers produced through CDPEM program.